The influence of incentives, job motivation, and job satisfaction on performance of offices of danau kerinci district - Wazirman Wazirman; Nurmawati Nurmawati; Pretti Pretti; Yandi Yandi (Indonesian Institute for Counseling, Education and Theraphy, 2022)
This study aims to see the effect of (1) Incentives for the performance of the employees of the Danau Kerinci sub-district office (2)Work motivation on the performance of the employees of the Danau Kerinci Sub-District Office (3) Job satisfaction on the performance of the employees of the Danau Kerinci District Office (4) Incentives, work motivation and job satisfaction have a joint effect on the performance of the employees of the Danau Kerinci Sub-District Office. The population in this study is allThere are 30 employees of the Danau Kerinci Sub-district Office. Techniques for determining the number of samplesusing total sampling.The results of this study indicate that (1) Incentivehas a positive significant effect on the performance of the employees of the Danau Kerinci Sub-district Office (2) Work motivationprovide a positive influence on the performance of the employees of the Danau Kerinci Sub-district Office (3) Job satisfactionprovide a positive influence on the performance of the employees of the Danau Kerinci Sub-district Office (4) Incentives, work motivation and job satisfactionjointly have a positive effect on the performance of the employees of the Danau Kerinci District Office